Report on the Simulation of Low Carbon Green Growth Policies, including the Results of Impact Assessment and Final Policy Recommendations - World Bank (Washington, DC, 2016)
This assessment presents a synthesis of analysis to contribute to the definition of a lower carbon and greener growth path for Romania to 2050. The objective of Romania’s green growth path is to implement mitigation actions and undertake needed adaptation while preserving growth and employment. Romania has maintained a steady growth in output while containing the growth of its greenhouse gas (GHG) emissions. From now to 2050, real incomes in Romania are expected to continue to grow, and its carbon emissions are expected to continue declining. Romania can meet the targets of the green scenario with only modest costs to growth and employment, European Union (EU) emissions trading for energy-intensive sectors sets a uniform price for GHG allowances, which generates an efficient allocation across countries of mitigation actions in those sectors. The difficulty of meeting the tighter targets for mitigation set out in the green and super green scenarios will be eased significantly by improvements in energy efficiency. Proactive measures to promote smart urban development in Bucharest and other urban areas, including more compact city design, transport-oriented development that changes modal-split, upgrades to a more efficient vehicle stock, and policies promoting building efficiency upgrades, can deliver sizable reductions in annual energy spending and emission levels.